Copper local structure in spinel ferrites determined by X-ray absorption and Mössbauer spectroscopy and their catalytic performance. (January 2019) - Rocha, A.K.S.; Magnago, L.B.; Pegoretti, V.C.B.; de Freitas, M.B.J.G.; Lelis, M.F.F.; Fabris, J.D.; Porto, A.O.
Graphical abstract: Highlights: Copper spinel ferrites with different copper contents were prepared by a co-precipitation method. Copper local atomic structures were investigated by X-ray absorption spectroscopy, X-ray powder diffraction and 57Fe Mössbauer spectroscopy. The catalytic efficiency of copper spinels were tested as catalysts towards methylene blue dye degradation via photo-Fenton reaction. X-ray absorption data showed that the increase of copper concentration induced a change on its location in the spinel structure from the octahedral to the tetrahedral coordination sites. Abstract: Magnetite and copper spinel ferrites were prepared by co-precipitation method and characterized by X-ray powder diffraction, 57 Fe Mössbauer spectroscopy and scanning electron microscopy. XRD data showed the formation of cubic structure with particle sizes ranging from 30 to 23 nm. According to 57 Fe Mössbauer data the obtained magnetite as well as copper ferrites were partially oxidized. The occupancy of Cu 2+ changes from tetrahedral to octahedral sites with the increase of copper content, as observed by the analysis of 57 Fe hyperfine parameters and XAS data. Catalytic behavior of the obtained samples were investigated towards methylene blue dye degradation using photo-Fenton reactions.